Experiential cartography and the significance of "untranslatable" words. (August 2018) - Lomas, Tim
Mainstream psychology can be regarded as largely Western-centric, with its concepts and priorities biased towards Western ways of thinking and understanding. Consequently, the field would benefit from greater cross-cultural awareness and engagement. To that end, this article offers one means of engagement, the study of "untranslatable" words (i.e., terms without an exact equivalent in another language, in our case English). A key function of language is that it offers a "map" that allows us to understand and navigate the world. In that respect, such words point to cultural variation in the maps we use, and even to variation in the actual territory mapped. The paper concludes with suggestions for why and how psychology could benefit from engaging with such words.